The money mule syndicate / Mohd Shafiz Saharan, Mohd Fazil Jamaludin and Khairul Azfar Adzahar - Saharan, Mohd Shafiz; Jamaludin, Mohd Fazil; Adzahar, Khairul Azfar (Universiti Teknologi MARA, Kedah, 2022)
The financial system is threatened globally by the money mule issue. Money mules are used by criminals, including scammers, fraudsters, and online hackers, to launder their stolen money (Moore et al., 2009; Richet, 2013). Money mule refers to unwitting victims tricked by scammers into using their bank accounts to launder stolen or illegal money. Usually, a small amount of the cash is transported as a payment for the mule's services. In addition, a mule account is when an individual or company permits others to handle their bank accounts by passing over their ATM card PIN or internet banking password to criminals for them to receive money from fraudulent activity (Esoimeme, 2020; Raza et al., 2020; Saufi Zulqaram Rosli et al., 2022). Using a money mule is primarily intended to conceal the money trail and thwart any attempts to investigate the underlying illicit activities. It is one of the money laundering issues plaguing banking organisations and necessitates considerable compliance effort (Esoimeme, 2020). An individual known as a money mule is not a member of the criminal organisation but is employed and placed within it to obstruct law enforcement efforts. They block the money trail, and the criminals benefit from money laundering. A money mule receives money in their bank account from a third party, takes it out in cash or moves it to another account, and gets paid a commission for the transfer. In addition to running themselves, mules set up businesses or bank accounts in their names run by criminal organisations to launder money. Money mules are complicit in the crime since they help to launder the illicit money. The payoff is modest compared to the danger incurred by the money mule.